2006
DOI: 10.2174/157489106778777673
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Development of Inactivated Virus Vaccines

Abstract: Vaccine discovery stands out as one of the public health interventions that has achieved the greatest impact in world's health. Vaccination is the most effective means of disease prevention, especially for viral infections. Starting with the use of smallpox vaccine by Jenner in the late 1700s, the technology for vaccine development has seen numerous advances. Currently, vaccines available for human viral illness are based on live attenuated (e.g. measles, mumps, and rubella), inactivated (e.g. hepatitis A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 0 publications
0
34
0
3
Order By: Relevance
“…For many years, the standard approach to preparing inactivated vaccines has been to inactivate the pathogens with formaldehyde or BPL 3,7 . In particular, the utility of formaldehyde as the standard mode of pathogen inactivation for vaccine development has been questioned 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years, the standard approach to preparing inactivated vaccines has been to inactivate the pathogens with formaldehyde or BPL 3,7 . In particular, the utility of formaldehyde as the standard mode of pathogen inactivation for vaccine development has been questioned 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the utility of formaldehyde as the standard mode of pathogen inactivation for vaccine development has been questioned 3 . Other inactivation approaches such as psoralens, ethylenimine and nonionic detergents have also been tested for development of various vaccines, but these are believed to have disadvantages similar to formaldehyde or BPL in terms of chemical modification of immunogenic proteins 3,7 . In contrast, we have found that H 2 O 2 represents a new and versatile platform for the development of inactivated vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivated and live attenuated vaccines are based on the antigenicity of killed and weakened versions of the virus, respectively. Inactivated vaccines may include whole inactivated virus particles, specific components derived from the virus or toxoids that are chemically modified to destroy their pathogenicity (Stauffer et al, 2006). China National Biotec Group already has some inactivated vaccine candidates available for testing; their immunogenicity and efficacy are currently under evaluation in experimental animals.…”
Section: Inactivated Vaccines and Live Attenuated Vaccinesmentioning
confidence: 99%
“…The above‐mentioned requirements for vaccine improvement may be achieved by altering the method of inactivation. A large number of studies in the past have dealt with methods of virus inactivation in relation to preserving immunogenicity (reviewed in Ada and Stauffer and colleagues 85 , 86 ). The use of γ‐irradiation as an alternative method to chemical inactivation has been suggested several times in the literature, based on the view that organisms can be rendered incapable of reproduction primarily by damage to genetic material, rather than by structural destruction of proteins 87 .…”
Section: γ‐Ray Sterilization As a Superior Inactivation Methods For Inmentioning
confidence: 99%